The Potential of Video Vignettes to Promote Diagnostic Skills of Prospective Teachers at Vocational Schools - Teresa Giek; Philipp Eichentopf; Jürgen Seifried; Andrea Burda-Zoyke (Vocations and Learning, 2025)
The ability to evaluate teaching situations effectively is a critical component of vocational school teachers' professional competencies, particularly in diagnosing students' learning difficulties and potential in heterogeneous classrooms. Inclusive diagnostics serve as the foundation for adaptive teaching and individualized support, highlighting the importance of fostering these competencies in teacher education. To meet these demands and provide practice-oriented training, video-based teaching and learning formats are gaining increasing importance. In this context, video vignettes have been identified as promising tools for bridging the gap between teacher education and professional practice. In this context, we developed video vignettes to enhance student teachers' professional vision and inclusive diagnostic competencies. In our exploratory study, we analyzed both (1) the current state and (2) the development of student teachers' professional vision regarding inclusive diagnostics through their engagement with video vignettes in teacher training. The findings indicate that while prospective vocational school teachers find the description of the scenarios depicted manageable, providing well-reasoned justifications for their decisions presents greater difficulty but shows improvement with continued engagement. Furthermore, measurable changes both in competencies and in self-efficacy related to cognitive, linguistic, and behavioral aspects, are observed over the course of vignette-based interventions. These results highlight the efficacy of video vignettes as a pedagogical instrument in advancing professional vision and inclusive diagnostic skills within the framework of teacher education programs.
Keywords: 370; Video vignettes; Teacher education; Professional vision; Pedagogical diagnostics; Competence development; Inclusion